Potential therapeutic benefits of unconventional oils: assessment of the potential in vitro biological properties of some Rubiaceae, Cucurbitaceae, and Brassicaceae seed oils - Fratianni, Florinda; Amato, Giuseppe; De Feo, Vincenzo; d'Acierno, Antonio; Coppola, Raffaele; Nazzaro, Filomena (Frontiers in Nutrition, 2023)
Introduction - Seed oils are versatile in the food sector and for pharmaceutical purposes. In recent years, their biological properties aroused the interest of the scientific world. Materials and Methods - We studied the composition of fatty acids (FAs) and some in vitro potential therapeutic benefits of five cold-pressed commercial seed oils from broccoli, coffee, green coffee, pumpkin, and watermelon. We assayed the antioxidant activity (through the Diphenyl-1-Picrylhydrazyl (DPPH) and Azino-bis (3-ethylbenzothiazoline-6-sulfonic acid (ABTS) assays). Through the fatty acid composition, we calculated the atherogenicity index (AI) and thrombogenicity index (TI) to evaluate their potential impact on cardiovascular diseases. Furthermore, we assessed the in vitro anti-inflammatory capacity of the oils (evaluated through their effectiveness in preventing protein degradation, using bovine serum albumin as protein standard) and their ability to inhibit in vitro the activity of cholinesterases and tyrosinase, involved in Alzheimer and Parkinson neurodegenerative diseases. Lastly, we evaluated the capacity of the oils to inhibit the biofilm of some pathogenic bacteria. Results – The unsaturated fatty acids greatly predominated in broccoli seed oil (84.3%), with erucic acid as the main constituent (33.1%). Other unsaturated fatty acids were linolenic (20.6%) and linoleic (16.1%). The saturated fatty acids fraction comprised the palmitic (6.8%) and stearic acids (0.2%). Broccoli seed oil showed the best AI (0.080) and TI index (0.16). The oils expressed a good antioxidant ability. Except for the watermelon seed oil, the oils exhibited a generally good in vitro anti-inflammatory activity, with IC50 values not exceeding 8.73 mg. Broccoli and green coffee seed oil showed the best acetylcholinesterase inhibitory activity; coffee and broccoli seed oils were the most effective in inhibiting butyrylcholinesterase (IC50=15.7 g and 20.7g, respectively). Pumpkin and green coffee seed oil showed the best inhibitory activity against tyrosinase (IC50 2 g and 2.77 g, respectively). The seed oils inhibited the biofilm of some Gram-positive and Gram-negative bacteria; Staphylococcus aureus resulted the most sensitive strain. Such activity seemed related only in some cases to the capacity of the oils to act on the sessile bacterial cells' metabolism, as indicated by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) colorimetric method.